A Comprehensive View of Frozen Shoulder: A Mystery Syndrome - de la Serna, Daniel; Navarro-Ledesma, Santiago; Alayón, Fany; López, Elena; Pruimboom, Leo (Frontiers in Medicine, 2021)
Frozen shoulder is a common epidemiological affliction. Data acquired from people who suffer from this type of damage in other joints such as the hip, wrist and ankle also exist; although these syndromes are less common. Treatment for frozen shoulder is primarily physical (physiotherapy, manual therapy), secondary medical (corticosteroid injections) and finally surgical but with limited success. The difficulty in treating this type of condition successfully lies in the lack of knowledge about the risk factors involved and the pathophysiology underlying this mysterious syndrome. This review gives an overview of the current scientific position of frozen shoulder in terms of evolutionary factors, etiology, the different mechanisms of action involved, current treatment options and other possible interventions based on recent discoveries of pathophysiological mechanisms. The overall objective is to clarify several unknown aspects of a syndrome that affects up to 5% of the world's population.